In situ imaging of mitochondrial outer-membrane pores using atomic force microscopy - Layton, Bradley E (BioTechniques, 2004)
Here we describe a technique for imaging of the outer contours of the mitochondrial membrane using atomic force microscopy, subsequent to or during a toxic or metabolic challenge. Pore formation in both glucose-challenged and 1,3-dinitrobenzene (DNB)-challenged mitochondria was observed using this technique. Our approach enables quantification of individual mitochondrial membrane pore formations. With this work, we have produced some of the highest resolution images of the outer contours of the in situ mitochondrial membrane published to date. These are potentially the first images of the component protein clusters at the time of formation of the mitochondrial membrane transition pore in situ. With the current work, we have extended the application of atomic force microscopy of mitochondrial membranes to fluid imaging. We have also begun to correlate 3-D surface features of mitochondria dotted with open membrane pores with features previously viewed with electron microscopy (EM) of fixed sections